Ligational, analytical and biological applications on oxalyl bis(3,4-dihydroxybenzylidene) hydrazone - El-Asmy, Ahmed A.; El-Gammal, O.A.; Radwan, H.A.; Ghazy, S.E. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2010)
The molecular modeling and parameters have been calculated to confirm the geometry of oxalyl bis(3,4-dihydroxybenzylidene) hydrazone, H 6L. The metal complexes of Cr 3+, VO 2+, ZrO 2+, HfO 2+, UO 2 2+ and MoO 2 2+ with H 6L have been prepared and characterized by partial elemental analysis, spectral studies (electronic; IR), thermal analysis and magnetic measurements. The data suggest the formation of polymer complexes with a unit [Cr(H 4L)(H 2O) 3Cl]·H 2O, [VO(H 4L)(H 2O) 2], [Hf(H 4L)(H 2O)]·H 2O [UO 2(H 4L)(H 2O) 2]·2H 2O [MoO 2(H 4L)] and [(ZrO) 2(H 2L)-(C 2H 5OH) 2]. The ligand behaves as a dibasic bidentate in all complexes except ZrO 2+ which acts as a tetrabasic tetradentate with the two ZrO 2+ ions. An octahedral geometry was proposed for the Cr 3+, HfO 2+, MoO 2 2+and UO 2 2+ complexes and square pyramid for VO 2+. The Cr 3+ is necessary to degrade the DNA of eukaryotic subject completely; the other complexes have little effect. H 6L was found suitable as a new reagent for the separation and preconcentration of ZrO 2+ ions from different water samples using flotation technique with satisfactory results.